Fatores associados ao consumo do álcool por adolescentes brasileiros : análise multinível - Gabira, Fernanda Garcia (2019)
Introduction: Alcohol consumption during adolescence is an important process and a major public health challenge because of its magnitude and associated consequences. Alcohol is a drug most used by adolescents according to WHO data, because it is a phase permeated by high contextual vulnerability, so it is a mistake that has as determined this consumption. Objective: To investigate factors associated with alcohol consumption in adolescence according to sociodemographic and geographic characteristics. Method: Data on Cardiovascular Risk in Adolescents (ERICA) were used, a sample of 74.589 adolescents aged 12 to 17 years, selected from 1.247 schools in 124 Brazilian municipalities. A dependent variable was the consumption of alcoholic beverages and as independent variables of socio-demographic, economic and geographic stratum. A univariate and previous descriptive analysis was performed for the variables of interest (dependent and independent). The level of the level of state capital (Level 1), level 2 (subject), level 2 (state capital). The analyzes were published in the statistical package R 3.4.3 (R Core Team, 2017). For the effect of sample design, corrected by post-stratification, in the regression, multilevel logistics used the MPLUS version 7 program. The significance level of all the tests was 5%. Results: Varieties associated with the consumption of alcoholic beverages were: the black / black race, schoolchildren residing only with the father, household aggregation medium and high, school enrolled in the afternoon shift and schoolchildren of rural regions. Associations for the regions of the South, Southeast, Bahia and DF. Conclusion: The study aimed to determine or investigate the factors of alcohol consumption in adolescence as sociodemographic and geographic characteristics. Also, the present study described how the consumption of alcoholic beverages compared to gender, age, race-color, living with the child, the person-to-room ratio, economic class, head of household mother, school type, study shift, school zone as well as the geographical stratum of the school by capitals of Brazilian states.